Evaluating the disaster preparedness of emergency medical service agencies in the world: A systematic literature review protocol - Mehdi Beyramijam; Hamid Reza Khankeh; Mehrdad Farrokhi; Abbas Ebadi; Gholamreza Masoumi; Hassan Nouri-Sari (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Disasters occur almost everywhere in the world, and preparation is essential. Preparedness is an effective approach for disaster management, and it is crucial for the health systems, especially the Emergency Medical Service (EMS) agencies. This systematic review will be conducted to assess the preparedness levels of EMS agencies in the world for the response to disasters and explore the key dimensions and strategies to enhance it. METHODOLOGY: This systematic literature review will be conducted to search comprehensively the articles published between 2000 and 2019 to explore the disaster preparedness of EMS Agencies. To this end, PubMed, Scopus, Web of Science, and Google Scholar will be thoroughly assessed. The following terms and expression will be used for searching the databases: "EMS" and other keywords "Disaster Preparedness," "Mass Casualty Incident," "Mass Gathering," "Terrorist incident," "Weapons of Mass Destruction," and CBRNE, Disaster, included: 'Emergency Preparedness, Preparedness, Readiness. DISCUSSION: To the best of our knowledge, no systematic review study has been conducted on disaster preparedness of EMS agencies in the world. This is the first study to address this gape. It will also explore the key dimensions of disaster preparedness in EMS services and the strategies to enhance their preparedness. CONCLUSION: Identifying the key dimensions of disaster preparedness is the first step in designing valid assessment tools to evaluate disaster preparedness of EMS service. This study will provide valuable guides for EMS administrators and researchers in an attempt to enhance of preparedness of EMS systems in disasters.